Adrenocortical and behavioural response to chronic restraint stress in neurokinin-1 receptor knockout mice - Delgado Morales, Raúl (2012)
Brain substance P and its receptor (neurokinin-1, NK1) have a widespread brain distribution and are involved in an important number of behavioural and physiological responses to emotional stimuli. However, the role of NK1 receptors in the consequences of exposure to chronic stress has not been explored. The present study focused on the role of these receptors in the hypothalamic-pituitary-adrenal (HPA) response to daily repeated restraint stress (evaluated by plasma corticosterone levels), as well as on the effect of this procedure on anxiety-like behaviour, spatial learning and memory in the Morris water maze (MWM), a hippocampus-dependent task. Adult null mutant NK1-/- mice, with a C57BL/6J background, and the corresponding wild-type mice showed similar resting corticosterone levels and, also, did not differ in corticosterone response to a first restraint. Nevertheless, adaptation to the repeated stressor was faster in NK1-/- mice. Chronic restraint modestly increased anxiety-like behaviour in the light-dark test, irrespective of genotype. Throughout the days of the MWM trials, NK1-/- mice showed a similar learning rate to that of wild-type mice, but had lower levels of thigmotaxis and showed a better retention in the probe trial. Chronic restraint stress did not affect these variables in either genotype. These results indicate that deletion of the NK1 receptor does not alter behavioural susceptibility to chronic repeated stress in mice, but accelerates adaptation of the HPA axis. In addition, deletion may result in lower levels of thigmotaxis and improved short-term spatial memory, perhaps reflecting a better learning strategy in the MWM. © 2011 Elsevier Inc.